Invasive Haemophilus Influenzae Type B Infections in Children with Cancer in the Era of Infant HIB Immunization Programs (1991–2014): A Report From the Canadian Immunization Monitoring Program Active. Issue 7 (July 2018) - McNair, Joanne; Smith, Alyssa; Bettinger, Julie A.; Vaudry, Wendy; Tan, Ben; Desai, Shalini; Halperin, Scott A.; Top, Karina A.
Abstract : We studied the epidemiology of Haemophilus influenzae type b infections among children with cancer admitted to Canadian pediatric hospitals. From 1991 to 2014, 13 cases among children with cancer were identified through active surveillance. Average age was 6.7 years. Six of 7 cases eligible for infant immunization were age-appropriately immunized (vaccine failures). Children with cancer may benefit from booster Hib immunization.